A cost analysis of remote monitoring in a heart failure program. Issue 3 (1st October 2016) - Williams, Cynthia; Wan, Thomas T. H.
ABSTRACT: In this study, we examine the cost per outcomes of remote monitoring services in home health care. The methodology followed case matched design via retrospective chart reviews. Results of the chi-square test suggest that there were no significant associations between the intervention and hospital readmissions, χ 2 = (1, n = 210, p -value = .71, phi = .71). An independent t -test compared group means of the number of skilled nursing visits and agency costs, p -value of .002 and .000, respectively, favoring the standard of care group. Based on this data set, the home care agency lost 153.46 for each hospital readmission in the intervention group. The cost of care complicated the agency's resources through an increase in nursing visits without offsetting the agency's investment into technology; the cost did not support remote monitoring as a financially viable option to the standard of care.